A study of working conditions in the heat-treating workshops - A. M. Lazarenkov (Литьë и металлургия, 2020)
The results of the study of working conditions in heat-treating workshops are presented. It is shown that the main production factors of working conditions are noise, vibration, dust, gas, air temperature, the intensity of infrared (thermal) radiation, the severity and intensity of the labor process.The results of the conducted research have shown that all workplaces have exceeded the permissible values for noise, the content of harmful substances in the air of the working environment, the intensity of infrared (thermal) radiation and the air temperature. It is noted that the work performed due to the severity and intensity of the labor process can negatively affect the health of employees.